Integrating Gamification in Expert Systems: A Novel Approach for Stress Disorder Diagnosis in Digital Mental Health - putri taqwa prasetyaningrum; Norshahila Ibrahim; Reny Yuniasanti; Ibnu Rivansyah Subagyo (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
The increasing prevalence of stress disorders highlights the need for innovative, accessible, and engaging diagnostic tools in mental health services. This study presents the design and implementation of a gamified expert system for diagnosing stress disorders, integrating gamification elements to enhance user engagement and reduce stigma. The system employs the forward chaining method to deliver high-accuracy, rule-based diagnoses while incorporating features such as points, rewards, and leaderboards to motivate user interaction.The system's development followed a user-centered design approach to ensure an intuitive interface aligned with user needs. Evaluation results demonstrated a diagnostic accuracy rate of 92%, validated by mental health professionals, alongside significant improvements in user engagement metrics, including session frequency and duration. Qualitative feedback indicated that gamification effectively reduced stigma and increased motivation for mental health assessments.These findings suggest that gamified expert systems can bridge gaps in accessibility and engagement in mental health services. This research contributes to the advancement of digital health technologies by providing practical insights into integrating gamification into expert systems to foster proactive mental health management.